Relationship between teat biometry and subclinical Mastitis in crossbred cows (Indian Journal of Animal Production and Management, 2024)
The investigation was undertaken on 110 Gir crossbred cows of different order of lactation and stage of lactation maintained at Research Cum Development Project on Cattle, MPKV, Rahuri. The overall least squares means of teat length and teat diameter were 6.88 ± 0.14 and 2.62 ± 0.06, cm respectively. The least squares analysis of variance showed significant (p2.5 cm. Highest occurrence (78.26%) of subclinical mastitis was found in cows of sixth and above lactation. Maximum occurrence of subclinical mastitis was noted in cows which were in late (46.15%) stage of lactation followed by early (40%) and mid (37%) stage of lactation. The incidence of subclinical mastitis was higher (51.61%) in cows who had teat end to floor distance of 55 cm (25%). It revealed that teat end to floor distance was important factor associated with occurrence of subclinical mastitis in Gir crossbred cows. The teat length had positive and significant association with incidence of subclinical mastitis in crossbred cows.
Keywords: Crossbred; Mastitis; Teat; Cylindrical; Pear; Funnel